Eficiência Econômica do Bicultivo de Peixes Em Viveiros Escavados Na Região Paulista do Médio Paranapanema - Furlaneto, Fernanda de Paiva Badiz; Esperancini, Maura Seiko Tsutsui [UNESP]; Bueno, Osmar de Carvalho [UNESP]; Ayroza, Luiz Marques da Silva (My University, 2009)
The study assessed the economic efficiency of the pacu with the piauçu cultivation in fishponds hollowed in the Middle Paranapanema region, State of São Paulo, 2007/08 crop. It was used the structures of the effective operational cost (EOC) and total operational cost (TOC) and five profitability indicators economic. The TOC per cycle ha-1 were US$ 12,182.90. The production cost of the pacu and of the piauçu it was US$ 1.20 kg-1 and US$ 1.40 kg-1, respectively. The gross income were US$ 17,077.30 ha-1, operational profit US$ 4,894.30 ha-1, gross margins 43.8% and profitability rate 30.3%. The break even point 6,125.40 kg ha-1 for the pacu and 805.90 kg ha-1 for the piauçu. The viable minimum module corresponded to 0,5 ha of mirror of water. Considering that in the Medium Paranapanema region the medium area of mirror of water for producer is of 0,6 ha, it was ended that this policulture is an alternative of income for enterprising rural regional.
Economic Efficiency of Fish Cultivation in the Middle Paranapanema Region, State of São Paulo
Keywords: Fishponds; Leporinus macrocephalus; Piaractus mesopotamicus; Production cost; Profitability indicators